PENYUSUNAN LAPORAN KEUANGAN PADA UMKM PEMANCINGAN GALATAMA LELE DENGAN MENGGUNAKAN ACCURATE - Suparti, Suparti; Lisnayati, Lisnayati; Supriyanto, Rudy (JURNAL LENTERA AKUNTANSI, 2023)
This research discusses the application of recording and preparing financial reports in the Tangerang Galatama Catfish Fishing UMKM, therefore the author has a research objective, namely to find out the recording of financial reports and to find out the process of preparing financial reports using Excel and Accurate in the Tangerang Galatama Catfish Fishing UMKM. The research method used was by means of literature study to obtain information regarding the title of the research taken and by means of field studies, namely direct observation of the company and interviews with related parties. Based on the results of observations, it shows that using Accurate can increase efficiency, reduce errors, and enable faster and more accurate financial reports to be prepared in real-time. Thus, this system is proven to be able to provide effective and structured accounting solutions for MSMEs.